Cardiovascular risk factors in children with hereditary loading - A. A. Muratov; M. K. Koshukeyeva; K. A. Aitbaev; E. S. Mainazarova; A. J. Alymkulova; J. T. Isakova (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence of CVRF in schoolchildren with a family history of atherosclerosis-related cardiovascular disease.Material and methods. The study included 106 schoolchildren aged 10 to 17 years. The main group consisted of children (n=55) with a family history of cardiovascular diseases (CVD) and the control group (n=51) — without hereditary loading. The study was conducted using a specially designed questionnaire, including medical history, clinical and laboratory data. Levels of total cholesterol, high density lipoproteins and triglycerides were determined with a Mindray kit using a photometric method on a BS-360E chemistry analyzer (Mindray).Results. There was a 60% of paternal family history of CVD and 34,5% — of maternal. Smoking was detected in 10,4%, sedentary life-style — in 83,6%, and a tendency to hypertension — in 33% of children. Dyslipidemia, as the main CVRF, was observed in 63,6% of children with a positive family history.Conclusion. The results of the study suggest that CVRF in adults is widespread among children. The prevalence of CVRF in children with family history of CVD is higher than in children with negative family history.